Adolescent social withdrawal, parental psychological control, and parental knowledge across seven years: A developmental cascade model. (June 2020) - Lin, Hua; Harrist, Amanda W.; Lansford, Jennifer E.; Pettit, Gregory S.; Bates, John E.; Dodge, Kenneth A.
Abstract: Introduction: Social withdrawal can be problematic for adolescents, increasing the risk of poor self-efficacy, self-esteem, and academic achievement, and increased levels of depression and anxiety. This prospective study follows students across adolescence, investigating links between social withdrawal and two types of parenting hypothesized to impact or be reactive to changes in social withdrawal. Methods: Adolescent social withdrawal and parenting were assessed across seven years in a U.S. sample, beginning when students were in 6th grade and ending in 12th grade. The sample consisted of 534 adolescents (260 girls and 274 boys, 82% Euro- and 16% African-American). Social withdrawal was assessed in four grades using at least two informants (teachers, mothers, and/or adolescents). Mothers' and fathers' psychological control and monitoring-related knowledge were assessed by adolescents at two time points. A developmental cascade analysis was conducted using structural equation modeling to assess how withdrawal and control-related parenting impact each other transactionally over time. Analyses included a test for gender differences in the model. Results: The cascade model revealed that, controlling for previous levels of social withdrawal and parenting, earlier social withdrawal positively predicted psychological control and negatively predicted monitoring knowledge, and earlier parental psychological control—but not monitoring knowledge—predicted later social withdrawal. No adolescent gender differences were identified in the associations between social withdrawal and parental knowledge. Conclusions: This study offers insight into the mechanisms by which adolescents become more or less withdrawn over time, and suggests psychological control as a point of psychoeducation or intervention for parents. Graphical abstract: Image 1